IMPLEMENTATION OF NADHIR ONLINE REGISTRATION SYSTEM IN BADAN WAKAF INDONESIA USING AGILE DEVELOPMENT METHODS - Muhammad Chamdani Sukron; Rizqi Putri Nourma Budiarti; Ahmad Syafiq Kamil (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2020)
The Indonesian Waqf Board is an independent state institution formed under law number 41 of 2004 concerning endowments. At present, nadhir registration service activities at the Indonesian Waqf Board are still carried out offline, which causes nadhir registration service activities to be inefficient and take a long time. From the above problems the authors make research "Implementation of the Nadhir Online Registration System Using Agile Development Methods" which can help the Indonesian Waqf Board in nadhir registration activities in the Indonesian Waqf Board. This research uses agile development methods that focus on personal interactions, software functionality, collaboration with clients, responses to change. The results based on experiment are in the form of a website-based nadhir registration information system that features online registration, file upload, disposition, file verification, recommendations, approving and printing certificates that can help the process of registering nadhir in Indonesian Waqf Board. The system test results obtained from the usability variable 82% so it can be concluded that the system is feasible to use.